Extrusion dwell time and its effect on the mechanical and thermal properties of pitch/LLDPE blend fibres - Aldosari, Salem Mohammed; Rahatekar, Sameer S. (MDPI, 2021)
Mesophase pitch-based carbon fibres have excellent resistance to plastic deformation (up to 840 GPa); however, they have very low strain to failure (0.3) and are considered brittle. Hence, the development of pitch fibre precursors able to be plastically deformed without fracture is important. We have previously, successfully developed pitch-based precursor fibres with high ductility (low brittleness) by blending pitch and linear low-density polyethylene. Here, we extend our research to study how the extrusion dwell time (0, 6, 8, and 10 min) affects the physical properties (microstructure) of blend fibres. Scanning electron microscopy of the microstructure showed that by increasing the extrusion dwell from 0 to 10 min the pitch and polyethylene components were more uniformly dispersed. The tensile strength, modulus of elasticity, and strain at failure for the extruded fibres for different dwell times were measured. Increased dwell time resulted in an increase in strain to failure but reduced the ultimate tensile strength. Thermogravimetric analysis was used to investigate if increased dwell time improved the thermal stability of the samples. This study presents a useful guide to help with the selection of mixes of linear low-density polyethylene/pitch blend, with an appropriate extrusion dwell time to help develop a new generation of potential precursors for pitch-based carbon fibres.
Keywords: blend; extrusion; dwell time; morphology; carbon-fibres; mesophase pitch; polyethylene